The effect of lactose, NaCl and an aero/anaerobic environment on the tyrosine decarboxylase activity of Lactococcus lactis subsp. cremoris and Lactococcus lactis subsp. lactis - Buňková, Leona; Buňka, František; Pollaková, Eva; Podešvová, Tereza; Dráb, Vladimír (International journal of food microbiology, 2011)
The aim of this work was to study, under model conditions, combined effects of the concentration of lactose (0-1% w/v), NaCl (0-2% w/v) and aero/anaerobiosis on the growth and tyramine production in 3 strains of Lactococcus lactis subsp. lactis and 2 strains of L. lactis subsp. cremoris. The levels of the factors tested were chosen with respect to the conditions which can occur during the real process of natural cheese production, including the culture temperature (10 ± 1°C). In all strains tested, tyrosine decarboxylation was most influenced by NaCl concentration; the highest production of tyramine was obtained within the culture with the highest (2% w/v) salt concentration applied. Two of the strains L. lactis subsp. lactis produced tyramine only in broth with the highest NaCl concentration tested. In the remaining 3 strains of L. lactis, tyramine was detected under all conditions applied. The tested concentration of lactose and aero/anaerobiosis had a less significant effect on tyramine decarboxylation. However, it was also found that at the same concentrations of NaCl and lactose, a higher amount of tyramine was detected under anaerobic conditions. In all strains tested, tyramine decarboxylation started during the active growth phase of the cells.
Keywords: Anaerobiosis; laktosa; Lactose; teplota; sýr; anaerobióza; chlorid sodný; tyramin; Sodium Chloride; Temperature; Tyramine; Lactococcus lactis; tyrosindekarboxylasa; Aerobiosis; aerobióza; Tyrosine Decarboxylase; Cheese